Human nutrition and adaptation in Brazilian Amazon fishing areas: contributions to health policies - Gilberto Ferreira de Souza Aguiar (Boletim do Museu Paraense Emílio Goeldi. Ciências Humanas, 2006)
The search for equity in access to services is presently an important principle in public policies for health in Brazil. Social inequalities in the Amazonia occur at high levels comparatively to the other regions in the country; and, within Amazonia, they particularly affect rural communities. The present study aims to appreciate associations between food and nutritional profile, adaptive strategies, and epidemiology in these communities, specially in areas of artisanal fishery, and also to suggest general lines of appropriated health policies. The construction of a context of equitable assistance and of sustainable health, without significant damage to biodiversity, depends on the capacity of public power in exploring the relationships between use and management of natural resources and the quality of life of riverine man.